Null-space impedance control of 7-degree-of-freedom redundant manipulators based on the arm angles. (29th May 2020) - Xiong, Genliang; Zhou, Yang; Yao, Jiankang
An impedance control method in null-space for 7-degree-of-freedom redundant manipulators is presented in this article. The null-space impedance motion of the redundant manipulator was described in the angle domain and a null-space impedance equation was established. To successfully obtain joint angular velocity, a high-gain observer is designed. The stability of the proposed control method was proved based on passive theory. The proposed null-space impedance control method not only preserved the Cartesian space impedance characteristics of the redundant manipulator but also achieved null-space impedance control. When the manipulator interacted with the outside world, the position error of the end effector asymptotically converged due to the self-motion of the manipulator. Simulations and experiments of the general impedance control method and the proposed impedance control method verified the effectiveness of the proposed method.